Production of Autopolyploid Lowland Switchgrass Lines Through In Vitro Chromosome Doubling. - Yang, Zhiyong; Shen, Zhengxing; Tetreault, Hannah; Johnson, Loretta; Friebe, Bernd; Frazier, Taylor; Huang, Lin-kai; Burklew, Caitlin; Zhang, Xin-Quan; Zhao, Bingyu (My University, 2014)
Switchgrass is considered one of the most promising energy crops. However, breeding of elite switchgrass cultivars is required to meet the challenges of large scale and sustainable biomass production. As a native perennial adapted to North America, switchgrass has lowland and upland ecotypes, where most lowland ecotypes are tetraploid (2n=4x=36), and most upland ecotypes are predominantly octoploid (2n=8x=72). Hybridization between lowland and upland switchgrass plants could identify new cultivars with heterosis. However, crossing between tetraploid and octoploid switchgrass is rare in nature. Therefore, in order to break down the cross incompatibility barrier between tetraploid lowland and octoploid upland switchgrass lines, we developed autoployploid switchgrass lines from an anueploid lowland cv. Alamo. In this study, colchicine was used in liquid and solid mediums to chemically induce chromosome doubling in embryogenic calli derived from cv. Alamo. Thirteen autopolyploid switchgrass lines were regenerated from seedlings and identified using flow cytometry. The autoplyploid switchgrass plants exhibited increased stomata aperture and stem size in comparison with the cv. Alamo. The most autooplyploid plants were regenerated from switchgrass calli that were treated with 0.04 % colchicine in liquid medium for 13 days. One autopolyploid switchgrass line, VT8-1, was successfully crossed to the octoploid upland cv. Blackwell. The autoployploid and the derived inter-ecotype hybrids were confirmed by in situ hybridization and molecular marker analysis. Therefore, the results of this study show that an autopolyploid, generated by chemically induced chromosome doubling of lowland cv. Alamo, is cross compatible with upland octoploid switchgrass cultivars. The outcome of this study may have significant applications in switchgrass hybrid breeding.
Citation: Yang, Z., Shen, Z, Tetreault, H., Johnson, L., Friebe, B., Frazier, T., Huang, L. K., Burklew, C., Zhang, X. Q., & Zhao, B. (2014). Production of Autopolyploid Lowland Switchgrass Lines Through In Vitro Chromosome Doubling. Retrieved from http://krex.ksu.edu
Keywords: Bioenergy; Switchgrass; Autopolyploids; Chromosome doubling; Cytogenetics; Biofeedstocks